2022
DOI: 10.3390/biomedicines10092175
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability in Type 1 Diabetes Mellitus Pregnancies—Novel Parameters in Predicting Large-for-Gestational-Age Neonates: A Prospective Cohort Study

Abstract: Pregnancies with type 1 diabetes mellitus (T1DM) have a high incidence of large-for-gestational-age neonates (LGA) despite optimal glycemic control. In recent years, glycemic variability (GV) has emerged as a possible risk factor for LGA, but the results of the conducted studies are unclear. This study analyzed the association between GV and LGA development in pregnancies with T1DM. This was a prospective cohort study of patients with T1DM who used continuous glucose monitoring (CGM) during pregnancy. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For expectant mothers with type 1 diabetes, this might mean missed opportunities for timely interventions or adjustments in their diabetes management plan, potentially impacting both maternal and foetal health. Furthermore, the importance of consistent CGM use in pregnancy is underscored by the dynamic nature of glucose levels during this period[ 37 ].…”
Section: Correlation Of Each Parameter To Pregnancy and Neonatal Outc...mentioning
confidence: 99%
See 1 more Smart Citation
“…For expectant mothers with type 1 diabetes, this might mean missed opportunities for timely interventions or adjustments in their diabetes management plan, potentially impacting both maternal and foetal health. Furthermore, the importance of consistent CGM use in pregnancy is underscored by the dynamic nature of glucose levels during this period[ 37 ].…”
Section: Correlation Of Each Parameter To Pregnancy and Neonatal Outc...mentioning
confidence: 99%
“…The clinical implications of GV during pregnancy are profound. GV has been identified as a potential risk factor for pregnancy complications, such as large for gestational age (LGA) infants[ 37 ]. Studies have shown that women with GDM exhibit higher GV, as indicated by increased SD and mean amplitude of glycaemic excursion (MAGE) values[ 28 ].…”
Section: Correlation Of Each Parameter To Pregnancy and Neonatal Outc...mentioning
confidence: 99%
“…In addition, future studies should evaluate the timing of initiation and role of CSII versus MDI in reducing glycemic variability to improve time in range, including prevention of prandial hyperglycemia, in mitigating adverse pregnancy outcomes. 71…”
Section: Strengths Limitations and Future Areas Of Studymentioning
confidence: 99%
“…These aforementioned variables that contribute to the complexity of CSII use may ultimately contribute to fetal hyperinsulinemia, overgrowth, and resultant LGA compared to MDI users. 28,[69][70][71] However, the available data do not elucidate the relative contributions of these challenges with CSII therapy to the greater risk of LGA. Similarly, the available data do not account for the contribution of these complex CSII variables to fetal hyperinsulinemia and associated neonatal hypoglycemia risk in those who initiate CGM prior to pregnancy.…”
Section: Main Findings and Comparison With Existing Literaturementioning
confidence: 99%